2018
DOI: 10.1016/j.ijpharm.2018.08.051
|View full text |Cite
|
Sign up to set email alerts
|

Impact of ring size and drug loading on the pharmacokinetics of a combination dapivirine-darunavir vaginal ring in cynomolgus macaques

Abstract: This work investigates the impact of vaginal ring size and drug loading on the in vitro release, safety, ease of fit, and pharmacokinetics in cynomolgus macaques of matrix-type silicone elastomer vaginal rings containing a combination of the non-nucleoside reverse transcriptase inhibitor dapivirine and the protease inhibitor darunavir. Drug-free and drug-loaded vaginal rings having three different geometries were manufactured by reaction injection molding. In vitro drug release was assessed using both a solven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 57 publications
0
20
0
Order By: Relevance
“…Just as for dissolution testing of oral doage forms, agitation rates are known to significantly impact in vitro drug release from vaginal rings, although only very limited data on this topic has been reported in the literature [51,52]. [7,26,62,63], and organic solvent/water mixtures [7,[62][63][64][65][66][67][68]. Although polyethylene glycol/water mixures were used in many early studies, these media see limited use today.…”
Section: Stirring or Agitation Of The Release Mediummentioning
confidence: 99%
See 1 more Smart Citation
“…Just as for dissolution testing of oral doage forms, agitation rates are known to significantly impact in vitro drug release from vaginal rings, although only very limited data on this topic has been reported in the literature [51,52]. [7,26,62,63], and organic solvent/water mixtures [7,[62][63][64][65][66][67][68]. Although polyethylene glycol/water mixures were used in many early studies, these media see limited use today.…”
Section: Stirring or Agitation Of The Release Mediummentioning
confidence: 99%
“…A matrix-type silicone elastomer vaginal ring releasing dapivirine, an experimental nonnucleoside reverse transcriptase inhibitor, has been in development since 2002 and has recently completed Phase III clinical testing as a female-controlled method for prevention of HIV-1 infection[68,[105][106][107]. Numerous journal articles have reported in vitro release testing of vaginal rings containing either dapivirine alone or dapivirine in combination with another drug, most using a shaking incubator or shaking water-bath method[7,16,23,62,64,66,68,95,107]. Since dapivirine has very poor solubility in aqueous media (<<1 μg/mL)[67,96], much of the reported in vitro release data for the vaginal ring describes use of a 1:1 isopropanol/water mixture in which dapivirine has greatly enhanced solubility[7,64,68,97,107].…”
mentioning
confidence: 99%
“…Consequently, the volumes of test media used for in vitro drug release experiments with macaque-sized IVRs are often significantly smaller than those used in human IVR experiments [24,37,38,39,40]. The reported agitation speeds in shake-flask experiments range from 60 rpm [31,35,36,37,38,39,40,41,42,43,44,45,46,47,48,70,75,78,79,80] through 80 rpm [51,52,53,54,73], 100 rpm [10,56,57,58,71] and 110 rpm [17] to 130 rpm [34,49,50,81,82].…”
Section: Current In Vitro Methods For Evaluating Drug Release Of Imentioning
confidence: 99%
“…A follow-up phase III trial (MTN-020/ASPIRE) [51] showed that 19% (6/32) women who acquired HIV-1 during the previous trial experienced virological failure. Results of a number of clinical trials addressing the impact of DPV ring on adherence [52], social concerns [53,54], pharmacokinetics in lactating women [55], pregnancy [56], and ring size [57] have been reported. Several other trials are in advanced stages.…”
Section: La Antivirals Targeting Hiv-1 Rtmentioning
confidence: 99%